Drug-resistant bacterial infections: we need urgent action and investment that focus on the weakest link. - Dolecek, C; Shakoor, S; Basnyat, B; Okwor, T; Sartorius, B (Public Library of Science, 2022)
Despite high mortality and morbidity, drug-resistant bacterial infections remain the forgotten pandemic. We argue for strengthening of diagnostics, WASH (water, sanitation, and hygiene) and infection prevention and control to reduce drug-resistant infections, as an integral part of sustainable high-quality health services, particularly in low- and middle-income countries.